cis-element combinations determine phenylalanine ammonia-lyase gene tissue-specific expression patterns. - Leyva, A (1992)
The bean phenylalanine ammonia-lyase gene 2 (PAL2) is expressed in the early stages of vascular development at the inception of xylem differentiation, associated with the synthesis of lignin precursors. This is part of a complex program of developmental expression regulating the synthesis of functionally diverse phenylpropanoid natural products. Analysis of the expression of PAL2 promoter-beta-glucuronidase gene fusions in transgenic tobacco plants showed that functionally redundant cis elements located between nucleotides -289 and -74 relative to the transcription start site were essential for xylem expression, but were not involved in expression in leaf primordia and stem nodes or in establishing tissue specificity in petals. The -135 to -119 region implicated in xylem expression contains a negative element that suppresses the activity of a cryptic cis element for phloem expression located between -480 and -289. The functional properties of each vascular element are conserved in stem, petiole, and root, even though the xylem and phloem are organized in different patterns in these organs. We conclude that the PAL2 promoter has a modular organization and that tissue-specific expression in the vascular system involves a negative combinatorial interaction, modulation of which may provide a flexible mechanism for modification of tissue specificity.